Participation Patterns on Hot Spring Sites Tourism Management in Western Thailand. - Chuamuangphan, Nipon (Journal of Management Science Nakhon Pathom Rajabhat University, 2019)
This research aimed to study the tourism management in hot spring sites in the western Thailand. The study was conducted using qualitative approach, in collaboration with participation from local communities. The fieldwork combines varied sources of data gathering techniques including in-depth interviews, focus groups, surveys, and observations. The samples were stakeholders in relation to tourism development such as governmental organizations, entrepreneurs, local shop owners, community leaders and members, and individual persons relevant to management of three hot spring destinations in western Thailand. The collected data from interviews were analyzed, interpreted and reported using content analysis and descriptive explanation methods. The results showed that: 1) There were three sites that were different from each other: 1) be managed by local community; 2) be managed by sub-district organization and 3) be managed by forestry department. 2) All of the three hot spring sites, in fact, were outstanding in terms of their local identities and natural resources which were suitable for developing into tourism destinations. However, they were not deeply focused to be used for health tourism at the sites. 3) In terms of tourism patterns, the three sites are considered as health tourism destinations which combined health tourism activities with other tourism resources and activities both in the area and nearby destinations in order to encourage the use of hot springs in each site. 4) The models for local participation and hot spring health tourism development in each study sites were different depending on the organizations that manage the area. For example, some sites were took care by the national park. Some were controlled by the Tambon Administration Organization (TAO). And some were locally managed by the community members. As a result the levels of participation in each site were different. For the one managed by local community, participation level of local residents is higher than the other authorities, for instance. Moreover, a hot spring tourism master plan should be launch as a guideline for tourism planning and management of hot spring destinations throughout Thailand. This master plan will help each destination to better plan and set the appropriate direction of hot spring tourism development which will benefit to the sustainability of the resources and the conservation of local identity and uniqueness. Article history : Received 8 July 2018 Revised 1 September 2018 Accepted 5 September 2018 SIMILARITY INDEX = 1.77